The Right to be Forgotten: Regulation of Personal Data Deletion in Indonesia - Ni Kadek Dhea Ardi Prabasari; Kadek Januarsa Adi Sudharma; Michael Angelo (KRTHA BHAYANGKARA, 2024)
The purpose of this paper is to analyze the regulation of personal data deletion in Indonesia as a form of protection for the right to be forgotten, and subsequently, the process of personal data deletion that exists in Indonesia. This paper discusses in detail the right to be forgotten. The research method used in this paper is normative legal research. It employs a conceptual approach and a legislative approach. The exploration of legal materials is conducted through document studies. The analysis in this paper is qualitative. The results of this research explain that the concept of the "right to be forgotten" refers to the individual's ability to request the deletion of their personal data from public databases, particularly information that could harm their reputation, privacy, or even social life. In the context of the European Union, this concept is outlined in Articles 7 and 8 of the Charter of Fundamental Rights of the European Union. Article 7 emphasizes the importance of respecting private and family life, which is a fundamental aspect of human rights. Meanwhile, Article 8 asserts the protection of personal data, stating that data must be processed fairly and for specific purposes, based on consent or a legitimate legal basis. The process of personal data deletion in Indonesia currently lacks specific regulations, thus relying on agreements between personal data owners and data controllers, in accordance with the principle of pacta sunt servanda.